IMPLEMENTASI SETS (Sceince, Environment, Technology, Social) TERHADAP LITERASI SAINS SISWA SDN 02 MOJOREJO MADIUN - Raras Setyo Retno; Diyan Marlina (Universitas Muria Kudus, 2018)
This sresearch aims to apply the SETS approach (Sceince, Environment, Technology, and Social) to improve scientific literacy through understanding science concepts, basic science process skills and scientific work on science learning for fifth grade students of SDN 02 Mojorejo Madiun City. The method used in this study is Classroom Action Research (CAR) which consists of 2 cycles. each cycle has 4 stages, namely planning, implementing, observing, and reflecting. the subjects in this study are fifth grade students of SDN 02 Mojorejo. The results of the study using the SETS approach (Sceince, Environment, Technology, and Social) in natural science learning showed an increase in scientific literacy, namely the maintenance of the science concept in terms of an increase in the class average value with a cycle value of 76.71 and an increase in 77 in cycle II. 81, there are basic process skills in students in the first cycle 30% and second cycle 60% and the scientific attitude of students in the second cycle that shows high categories, namely very good. Based on the results of the above study it can be concluded that the use of the SETS approach (Sceince, Environment, Technology, and Social) can improve scientific literacy through understanding the science concept, basic process skills and scientific work of students at SDN 02 Mojorejo Madiun in science learning with green plant matter.